2020
DOI: 10.1155/2020/7302727
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antioxidant Capacity of Lepidium sativum Seeds from Four Regions of Morocco

Abstract: Lepidium sativum seeds (LSS) from four regions of Morocco have been analyzed for their total chemical composition and antioxidant activities. In the seeds of this plant, the moisture content and yield were, respectively, 9.24–9.88% and 19.13–19.94% of dry weight. Chemical analysis of the seeds revealed amounts of fatty acids, sterols, and tocopherols. The most important fatty acids are linolenic acid (33%) and oleic acid (23%). The main sterol is β-sitosterol (50%); the vegetable oil of Lepidium sativum reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 23 publications
6
47
0
Order By: Relevance
“…This might be attributed to the multiple antioxidant and anti-inflammatory components of this plant, as shown in Tables 1 and 2 . This is supported by the recent work of Chatoui et al [ 62 ] who proved that the antioxidant activity of different extracts of L. sativum correlated significantly with their total flavonoids and other phenolic compounds. They suggested that L. sativum seeds could be used in food supplement preparations or as a food additive protecting against oxidative stress as a major signaling pathway related to glutamate excitotoxicity, a major etiological mechanism of almost all neurological disorders.…”
Section: Discussionsupporting
confidence: 63%
“…This might be attributed to the multiple antioxidant and anti-inflammatory components of this plant, as shown in Tables 1 and 2 . This is supported by the recent work of Chatoui et al [ 62 ] who proved that the antioxidant activity of different extracts of L. sativum correlated significantly with their total flavonoids and other phenolic compounds. They suggested that L. sativum seeds could be used in food supplement preparations or as a food additive protecting against oxidative stress as a major signaling pathway related to glutamate excitotoxicity, a major etiological mechanism of almost all neurological disorders.…”
Section: Discussionsupporting
confidence: 63%
“…Zia-Ul-Haq et al [ 36 ] reported that the aqueous extracts of Lepidium sativum seeds contain 0.0120 g GAE kg −1 . In addition, Chatoui et al [ 17 ] reported that the TPC of Lepidium sativum seeds’ aqueous extract contains 0.62 g GAE kg −1 of seed extract.…”
Section: Resultsmentioning
confidence: 99%
“…The mucilage seed extract of L. sativum showed good antioxidant activity determined with DPPH, which recorded 90%. Chatoui et al [ 17 ] noticed that the increase in TPC increases the antioxidant activity of the extract.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations